Antifungal properties of cardamom (Elettaria cardamomum) root exudate against Ganoderma boninense - Trimeiwardani, Anggita Aulya; Suwandi, Suwandi; Irsan, Chandra; Muslim, A.; Mulawarman, Mulawarman (Current Botany, 2025)
Ganoderma boninense, the causal agent of basal stem rot (BSR), poses a significant threat to oil palm plantations, resulting in severe economic losses and limited effective control options. This study investigates the antifungal properties of root exudates from three cultivars of cardamom (Elettaria cardamomum) as a sustainable alternative for BSR management. Root exudates were collected from eight cardamom samples and tested in vitro against G. boninense at concentrations of 1.25%, 5%, and 20% using malt extract agar (MEA) medium. Fungal growth inhibition was assessed by measuring colony diameter and electrical conductivity (EC) to evaluate membrane integrity. All exudate samples exhibited varying degrees of antifungal activity, with maximum inhibition across the tested concentrations ranging from 13.4% to 39.5%. The degree of inhibition depended on both the sample and concentration of the exudate, with no clear correlation between cultivar origin and antifungal efficacy. Increased EC values in treated media suggest that the inhibition mechanism involves hyphal membrane damage. This study is the first to report the antifungal activity of cardamom root exudates against G. boninense, highlighting their potential as natural agents for sustainable disease management in oil palm plantations.